TRANSLATION MODELS AND STRATEGIES IN THE TRANSFER OF EMOTIONAL SPEECH IN LITERARY CHARACTERS (KONFERENSIYA, 2025)
Emotional speech in literary characters’ dialogue constitutes a crucialexpressive layer through which authors encode psychological states, interpersonalrelationships, and ideological positions. Translating such emotionally chargeddiscourse presents a complex challenge, as emotional meaning is embedded not onlyin lexical units but also in syntactic structures, pragmatic markers, culturalconventions, and stylistic devices. This study explores the role of translation modelssuch as operational model, linguistic model, communicative-pragmatic models andtranslation strategies in the transfer of emotional speech in literary characters.Employing a qualitative comparative methodology informed by equivalence-based,communicative, functionalist, and pragmatic translation theories, the researchexamines how emotional meaning is preserved, transformed, or compensated intranslation. The findings indicate that emotional fidelity can only be achieved throughan integrative application of translation models combined with flexible strategiessuch as modulation, adaptation, compensation, and pragmatic substitution. The articleargues that emotional adequacy should be regarded as a fundamental criterion inevaluating literary translation quality